Comparative analysis of skin microbiome in acne lesions and healthy skin using 16S rRNA gene sequencing - Fadilah, Fadilah; Ikawati, Hartanti Dian; Karuniawati, Anis; Erlina, Linda; Agustina, Fitria; Paramita, Rafika Indah; Mohamad, Mohd Azrul Naim (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Acne vulgaris (AV) is a common dermatological disorder in adolescents, encompassing both non-inflammatory and inflammatory lesions, with growing evidence implicating the skin microbiome in its pathogenesis. This study analyzed skin lesion samples from 12 adolescents with AV using 16S rRNA high-throughput sequencing, with 12 healthy skin microbiome datasets as references. A total of 4.7 million high-quality reads were obtained, yielding 765,211 clean reads clustered into 1013 operational taxonomic units (OTUs). Microbial communities in lesions differed markedly from those in healthy skin. At the phylum level, lesions showed higher proportions of Bacteroidota and Bacillota, whereas healthy skin was dominated by Actinobacteria. At the genus level, lesions were modestly but significantly higher in Staphylococcus, Corynebacterium, and Peptoniphilus, while Cutibacterium was more abundant in healthy skin. Alpha diversity analysis revealed greater species richness and phylogenetic diversity in healthy skin, but higher evenness in lesions. Beta diversity confirmed significant differences in community structure. Functional prediction identified 391 metabolic pathways, 163 of which differed significantly; only three were enriched in lesions, while 160 were more abundant in healthy skin. Lipase activity was elevated in lesions, whereas hyaluronate lyase activity was higher in healthy skin. These findings indicate that healthy skin supports a richer and more functionally diverse microbial metabolism, whereas acne lesions are associated with reduced metabolic capabilities. Overall, the acne lesion microbiome exhibits reduced diversity, altered bacterial composition, and distinct functional traits compared to healthy skin, underscoring the role of microbial imbalance in acne and suggesting potential microbial targets for treatment